Challenging the Neoliberal Consensus: Islamic Populism as an Alternative Development Narrative in Post-Pandemic Malaysia - Honest Dody Molasy; Erwin Nur Rif’ah; Sus Eko Zuhri Ernada (Riviera Publishing, 2026)
This research examines the unprecedented electoral realignment in Malaysia’s 15th General Election (GE-15), widely referred to as the